2020
DOI: 10.32098/mltj.01.2020.07
|View full text |Cite
|
Sign up to set email alerts
|

Research proposal of a new clinic model for the interpretation of Lateral Elbow Pain: is it time to change?

Abstract: Background. Lateral Elbow Tendinopathy (aka Tennis Elbow or Lateral Elbow Pain), is characterized by a specific pain located in the lateral epicondyle and referred to the dorsal compartment of the forearm. Manual labour and forceful gripping activities can exacerbate pain, by restricting a patient's ability to work, train and perform simple daily tasks. In the framework of an aetiopathogenic complexity, a multimodal approach based upon the exclusive involvement of the common extensor tendon seems to be rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In an SR by Bisset et al (2005), 28 RCTs were analysed that dealt with the most effective interventions in the case of “lateral epicondylalgia” [ 27 ]. This terminological and conceptual transition underlines the shift from the biomedical pathology to the musculoskeletal disorder related to the bio–psycho–social sphere [ 11 , 27 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an SR by Bisset et al (2005), 28 RCTs were analysed that dealt with the most effective interventions in the case of “lateral epicondylalgia” [ 27 ]. This terminological and conceptual transition underlines the shift from the biomedical pathology to the musculoskeletal disorder related to the bio–psycho–social sphere [ 11 , 27 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following an evaluation algorithm proposed in a previous publication with the I-APPLEp algorithm [ 11 ], we believe that replacing the term “LEP” with “LEDs” is necessary. Our main goal is to describe and identify the lateral problems of the persistent-recalcitrant elbow—longer than three months—as an alternative to the old labels, among which are “epycondilitys,” “tennis elbow,” and “epycondilalgia.” Accordingly, we propose a modified version of the I-APPLE algorithm: LED-APP, the Lateral Elbow Disorders Approach (reported in Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined plain X-ray images and magnetic resonance images (MRI) in all elbows and found high intensity areas at the insertional sites of tendons in T2-weighted MRI or short tau inversion recovery (STIR) modes in 21 elbows, obvious synovial fringes of humeroradial joints in 3 elbows, complete full-thickness tears of common extensor tendons at the lateral epicondyles in 2 elbows, or a complete tear of the common flexor tendon at the medial epicondyle in one elbow of the patient after a previous surgery. We excluded cases affected with the arthritis or the osteoarthritis of elbows, rheumatoid arthritis, post-injury deformations of elbows, injuries or damages of extensor muscles located at forearm or cervical spondylo-radiculopathies, of which symptoms medial or lateral elbow pain was involved in for the correction of cases affected with enthesopathies or terminal stage of enthesopathies (26). A visual analog pain scale (VAS) or a modified Mayo Elbow Performance score (MEPS) were obtained for each elbow before the PRP therapies and at 3, 6 or 12 months after completion of the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of LEE is still controversial. Currently, it has even been suggested that LEE is a multi-factorial process with specific alterations of the psychosocial sphere [4]. Although LEE was initially considered a tendinitis, caused by tendon inflammation [5,6], LEE had its nomenclature changed to angio-fibroblastic tendinosis, since the histopathologic examination showed that the lesion is characterized by the presence of a dense population of fibroblasts, vascular hyperplasia, and disorganized collagen with few inflammatory cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%